Neuroendocrine mechanisms of grief and bereavement: A systematic review and implications for future interventions - Hopf, Dora; Eckstein, Monika; Aguilar-Raab, Corina; Warth, Marco; Ditzen, Beate (Journal of neuroendocrinology, 2020)
Summarized study results (including potential moderators/mediators).